Penerjemahan Kala Bahasa Inggris ke Bahasa Indonesia - Akhmad Hairul Umam (Cakrawala - Jurnal Humaniora, 2017)
The objective of this research is to know and to analyze the translation of tense in a novel as well as to see the level of equivalence between the source language and target language. The writer also wants to find out the procedures of translation used by the translator. This is a qualitative descriptive research that produces a data consisting of sentences of the present and the past form. Based on analysis of the translation for both the present and past tense has a very high level of acceptance between the source language and target language. While the translation procedure for this novel, the translator uses a lot of transposition, modulation, and adaptation. The writer also grouped sentences in verbal and nominal categories as well as justification of translation equivalence. The writer took 10 sentences randomly as the object of research analyzed by giving information, semantic analysis, and procedure of translation.